The Taxonomic Composition of Algae Flora on Soils - Abdusattarovna, To‘xtabayeva Yulduz; qizi, Sultonova Odina Iqboljon; qizi, Munisa Yusufjonova Abdumannob (Miasto Przyszłości, 2023)
The purpose of the research is to make a comparative analysis of the taxonomic composition of algae of the basic types of soils of the Fergana valley, and to determine their distribution in separate types of soils. Comparative analysis of taxonomic composition on the soils, exposed on algae in oak, brown soils; The main task of the research is to examine the distribution of algae along the profile of the soil, and to analyze the distribution of Alta taxa, particularly green-grass, diatomaceae, and green algae on the studied soils.